Best Market Decision Support System using Simple Additive Weighting Method - Rusda, Depi; Sari, Nadia (STMIK Banjarbaru, 2023)
Determining the location of the market to sell is very important because it affects the level of sales. To determine an effective market location, it is very necessary to evaluate local customers or visitors. In deciding the right business location requires several factors to support the selection of the best market in Sampit. The Simple Additive Weighting (SAW) method is a weighted addition method. This method requires the process of normalizing the decision matrix to a scale that can be compared with all the alternative ratings provided. It is highly recommended that traders trade on the PPM market. The data will be analyzed using the SAW method to determine the best market in Sampit. This research has clear objectives, namely to help traders choose the right market and improve economic welfare in Sampit. It is hoped that the results of this research can become a basis for further development in the field of decision support systems and market analysis methods.Keywords: Market; Decision Support System; Simple Additive Weighting MethodÂ AbstrakMenetukan lokasi pasar untuk berjualan merupakan suatu hal yang sangat penting karena mempengaruhi tingkat penjualan untuk menentukan lokasi pasar yang efektif maka sangat diperlukan penilaian dari para pelanggan atau penggunjung setempat. Dalam memetuskan lokasi usaha yang yang tepat memerlukan beberapa faktor untuk menunjang pemilihan pasar terbaik yang ada di Sampit. Metode Simple Additive Weighting (SAW) merupakan metode penjumlahan yang terbobot. Metode ini membutuhkan proses normalisasi matriks keputusan ke suatu skala yang dapat bandingkan dengan semua rating alternatif yang disediakan. Dengan ini sangat direkomendasikan para pedagang untuk berdagang di pasar PPM data akan dianalisis menggunakan metode SAW untuk menentukan pasar terbaik di kota Sampit. Penelitian ini memiliki tujuan yang jelas, yaitu membantu para pedagang untuk memilih pasar yang tepat dan meningkatkan kesejahteraan ekonomi di kota Sampit. Diharapkan bahwa hasil penelitian ini dapat menjadi landasan bagi pengembangan lebih lanjut dalam bidang sistem pendukung keputusan dan metode analisis pasar.